A thermally activated delayed blue fluorescent emitter with reversible externally tunable emission. Issue 5 (14th January 2016) - Rajamalli, Pachaiyappan; Senthilkumar, Natarajan; Gandeepan, Parthasarathy; Ren-Wu, Chen-Zheng; Lin, Hao-Wu; Cheng, Chien-Hong
Abstract : A TADF material containing a benzoylpyridine core and two meta carbazolyl groups shows externally switchable emission in the solid states and a high external quantum efficiency of 18.4% when used as a blue dopant in OLEDs. Abstract : A thermally activated delayed fluorescent (TADF) material containing two meta carbazolyl groups on the phenyl ring of the benzoyl-4-pyridine moiety was prepared and its luminescence showed a colour change from blue to green by external stimuli. The organic-blue-light-emitting device using this TADF dopant provided a high external quantum efficiency of 18.4%.